Ways of Describing the Degree of Physically Impaired Children, the Classification of Everyday Communication Skills and the Quality of Life Children with Cerebral Palsy - Marta Grabinska; Andrzej Kurylak; Ewa Barczykowska (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Cerebral palsy (CP) is a chronic and incurable disease, in which there is high possibility to significantly improve the patient’s condition. The formation of ways of describing the degree of physical impairment, the classification of everyday life communication skills or scales thanks to which there is high possibility to measure the quality of life in that specific group of patients, allows for thorough understanding of the needs, as well as systematic evaluation of therapeutic actions taken with respect to the patient with cerebral palsy. This work aims to provide the ways of describing a degree of physical impairment, the classification of everyday communication skills and the specific scales used to describe the quality of life patients with cerebral palsy. Research in the group of patients with ICP allows to learn the needs of patients and may be useful in channeling into development of the patients’ life quality from both clinical and social aspects. (JNNN 2014;3(4):183–187)